The Strategy Development of Marine Posture in Supporting the Main Task of Navy Using Swot and Borda Method (International Journal of Scientific Research and Management (IJSRM), 2022)
The Unitary State of the Republic of Indonesia is the largest archipelago country in the world. Its geological constellations which is the world cross position, place the marine territory of the national jurisdiction very strategically for Indonesia as well as for other countries. The marine posture capability can still be developed by enhancing the power and ability of the marines and optimizing the degree patterns. The marine posture development strategy can be done by learning the potential possible threats in the future and analyzing the marine posture conditions that must be improved to enhance national marine security. In this research, the strategy was analyzed with SWOT and BORDA methods. The result of this research is IFE value is 3.26 (3.00- 4.00) and the EFE value of 3.21 (3.00 – 4.00) which indicates that the marine posture is currently in a strong position. The position of marine posture strategy located at coordinates (3.26; 3.21) is Growth and Build. The marine posture development strategy lies in the position of quadrant III with coordinates (0.02;-0.11) that indicate st (strength threat) strategy, i.e. marine posture utilizes force to overcome threats.